2016
DOI: 10.1186/s40510-016-0151-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the stiffness characteristics of rapid palatal expander screws

Abstract: BackgroundThe aim of this study is to evaluate the mechanical properties of the screws used for rapid expansion of the upper jaw.MethodsTen types of expansion screw were assessed, seven with four arms: Lancer Philosophy 1, Dentaurum Hyrax Click Medium, Forestadent Anatomic Expander type “S”, Forestadent Anatomic Expander type “S” for narrow palates, Forestadent Memory, Leone A 2620-10 with telescopic guide, and Leone A 0630-10 with orthogonal arms; and three with two arms: Dentaurum Variety S.P., Target Baby R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Transverse maxillary deficiency deserves to be included in the distinctive occlusal pattern of class II malocclusion [ 1 9 ]. Therefore, the aim of the present pilot RCT was to evaluate the sagittal mandibular response induced by RME therapy in mixed dentition patients with class II malocclusion, comparing the effects of bonded RME and banded RME with a matched untreated class II control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transverse maxillary deficiency deserves to be included in the distinctive occlusal pattern of class II malocclusion [ 1 9 ]. Therefore, the aim of the present pilot RCT was to evaluate the sagittal mandibular response induced by RME therapy in mixed dentition patients with class II malocclusion, comparing the effects of bonded RME and banded RME with a matched untreated class II control group.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by several authors [ 6 9 ], widening the maxilla with rapid maxillary expansion often leads to spontaneous forward posturing of the mandible during the retention period. The orthopedic expansion removes occlusal interferences, allowing the mandible to posture forward, thus improving the sagittal relationships [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the manufacturer, the expansion per turn is 0.8 mm. Lombardo et al 20 , comparing different palatal expanders, reported that the Dentaurum Variety SP ® screw body size was 9.6 × 5 × 3mm, with a maximum expansion of 12 mm, and an arm diameter of 1.48 mm. From the initial activations, the screw exerted a force of 302 N (Newtons), and after 10 and 15 activations, it remained over 250 N. The stiffness of the screw remained high after 6-8 activations.…”
Section: Discussionmentioning
confidence: 99%
“…2021 Dentre os seus efeitos, tem-se um pequeno aumento espontâneo na largura do arco mandibular 8 . Além disso, conforme relatado por vários autores, o alargamento da maxila com ERM frequentemente leva à postura espontânea da mandíbula para frente durante o período de contenção 13 . Esse processo elimina a tendência de mordida cruzada vestibular com contato apenas das cúspides linguais dos dentes posteriores superiores com as cúspides vestibulares dos dentes inferiores posteriores e ao mesmo tempo melhora a relação no plano sagital.…”
Section: Introductionunclassified